ORGANIZATIONAL PRINCIPLES OF IMPLEMENTING THE MODEL OF FUTURE SPECIALISTS’ PERSONAL AND PROFESSIONAL DEVELOPMENT IN THE EDUCATIONAL AND INFORMATION ENVIRONMENT OF A TECHNICAL UNIVERSITY - Лузік, Ельвіра Василівна; Кокарєва, Анжеліка Миколаївна; Хоменко-Семенова, Леся Олексіївна (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
The study deals with the problem of professional training of future specialists at technical universities. The professional training is considered as a system process of purposeful personal changes during learning for realizing a full-fledged subjective position by students during their life. The use of a new intellectual and activity paradigm in the educational and information environment of a technical university has contributed to the formation of a certain type of future specialist’s consciousness, that has to perform the future professional activity in the best possible manner based on the reflexive approach and the implementation of the model of future specialist development in the educational and information environment of a technical university. The identification of the urgent issues of future specialists’ professional training has confirmed the researchers’ opinion that the psychological component has been practically excluded from the learning activity of the modern educational system, and this has led to the loss of a motivational component in obtaining a high-quality education; the lack of student’s self-criticism; students’ inability to identify and solve psychological problems of interpersonal relationships while learning. Therefore, the subjective characteristics of the student’s personality (personality development and needs, motives, goals) have to become the system-forming conditions for creating the model of students’ personal and professional development based on the reflexive approach in dynamic synergistic space with active (rigid and flexible) feedbacks. The main conceptual idea of the study is that instant identification and awareness by teachers and students of the real psychological tendencies taking place during studying, as well as the use of the corrective measures for the factors that destructively affect students’ learning activity and professional development, will facilitate combining the perspectives of personal and professional development, improving the efficiency and effectiveness of learning and their professional development while implementing the personal trajectory of life-long learning success